Efforts to Raise Legal Awareness For The People of Purwajaya Village to Have A Land Certificate as Authentic Proof of Land Ownership - Sitorus, Silvan Daniel; Maula, Naufal Rodiyatul; Makhron, Fiki Muzaki; Putra, Reza Alamsyah; Bilan, Hikmat; Lukmanulhakim, Zaidan; Arafat, Zarisnov (PT. Hafasy Dwi Nawasena, 2024)
Purwajaya Village, located in Tempuran District, Karawang Regency, faces significant problems related to land certification. Many of these villagers do not yet have land certificates, which shows a lack of awareness about the importance of certification as proof of legal ownership. To overcome this issue, the village government carried out the socialization of the Complete Systematic Land Registration Program (PTSL) to speed up the certification process. This research on efforts to increase public awareness uses a qualitative descriptive methodology. In this context, the theory of legal awareness by Soejono Sukanto is used as a reference to evaluate the effectiveness of the program. This theory includes four main factors: (1) knowledge of legal provisions, (2) recognition of legal provisions, (3) respect for legal provisions, and (4) compliance with legal provisions. Through the lens of this theory, PTSL socialization efforts are expected to increase community legal awareness and improve the problem of land certification in Purwajaya Village